Implementation of Corporate Social Responsibility Program on Community Welfare - Khenu Lather; Munnopule Khlise; Mashue Kinneth (Borong Newinera Publisher, 2021)
The purpose of this research is to evaluate the impact of the execution of the Corporate Social Responsibility program on the welfare of the local community. This research technique is descriptive qualitative, and it makes use of both primary and secondary data. The findings of this research show that the implementation of the Corporate Social Responsibility (CSR) program for the benefit of the community has not been successful, which is supported by a number of impediments to the success of these programs